‘Trendy’ cities: exploring the adoption of different types of social media by Portuguese municipalities - Silva, Tiago (2019)
What are the determinants of social media adoption by local government? This ongoing research provides a tentative answer to this question by analysing the 308 municipalities in Portugal. Extending previous analyses of Facebook and/or Twitter usage levels, we examine why local governments adopt a particular social media platform. More concretely, we explore, with statistical analyses, the determinants of the adoption of different types of social media. We investigate the adoption of three extremely popular social media (i.e. Facebook, Twitter and YouTube) as well as possible alternatives to those, more popular, applications. Since these platforms have distinct natures and can serve diverse purposes, we examine to what extent aspects such as local government’s commitment to transparency and participation, administrative capacity, media landscape, and socio-demographic and economic factors can explain the adoption of certain social media platforms. The results show that, indeed, demographic characteristics and administrative capacity are important factors for the adoption of less popular social media. Surprisingly, we also observe a geographical difference in municipalities’ social media adoption, with the south, in this regard, being ‘trendier’, or more innovative, than the north.